2018
DOI: 10.1016/j.repc.2017.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced life-threatening arrhythmias and sudden cardiac death: A clinical perspective of long QT, short QT and Brugada syndromes

Abstract: Sudden cardiac death is a major public health challenge, which can be caused by genetic or acquired structural or electrophysiological abnormalities. These abnormalities include hereditary channelopathies: long QT, short QT and Brugada syndromes. These syndromes are a notable concern, particularly in young people, due to their high propensity for severe ventricular arrhythmias and sudden cardiac death. Current evidence suggests the involvement of an increasing number of drugs in acquired forms of long QT and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 84 publications
0
13
0
2
Order By: Relevance
“…Th e patient did not accept the Some authors discuss the clinical importance of "drug-induced SBr", with interpretations that these cases represent "phenocopy" of the clinical pattern of spontaneous SBr type 1, that is, the drug-induced electrocardiographic manifestation did not have the same clinical significance. However, most authors prefer to be cautious until the real clinical role of these cases is defined, preferring the term "drug-induced SBr" [3][4][5][6] . There are reports that after an aborted cardiac arrest, both the presence of spontaneous and drug-induced SBr may have similar clinical meanings 7 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Th e patient did not accept the Some authors discuss the clinical importance of "drug-induced SBr", with interpretations that these cases represent "phenocopy" of the clinical pattern of spontaneous SBr type 1, that is, the drug-induced electrocardiographic manifestation did not have the same clinical significance. However, most authors prefer to be cautious until the real clinical role of these cases is defined, preferring the term "drug-induced SBr" [3][4][5][6] . There are reports that after an aborted cardiac arrest, both the presence of spontaneous and drug-induced SBr may have similar clinical meanings 7 .…”
mentioning
confidence: 99%
“…When the electrocardiographic pattern of SBr is inconclusive in baseline conditions (SBr types 2 and 3) and becomes typical after chemical sensitization (SBr type 1), we classify it as "drug-induced SBr type 1". This maneuver is routinely used in electrophysiology laboratories for diagnosis and risk stratification of SBr.However, the development of the electrocardiographic pattern of "drug-induced SBr" as a consequence of the adverse effect of the medication is much less known and discussed5 . Several reports in the literature have shown that in the same way that some medications can prolong the QT interval and generate the so-called "acquired long QT syndrome", some drugs can cause clinical and electrocardiographic manifestations compatible with SBr type 1[3][4][5] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 No entanto, o desenvolvimento de padrão eletrocardiográfico de "SBr droga-induzida" como consequência de efeito adverso de fármacos é muito menos conhecido e discutido5. De fato, diversos relatos na literatura têm demonstrado que, da mesma maneira que algumas drogas podem prolongar o intervalo QT e gerar a chamada "síndrome do QT longo adquirido", alguns fármacos podem provocar manifestações clínicas e eletrocardiográficas compatíveis com a SBr tipo 1 [3][4][5] .…”
unclassified
“…Alguns autores discutem a importância clínica da "SBr droga-induzida", havendo interpretações de que esses casos representam simplesmente "fenocópia" do padrão clínico da SBr tipo 1 espontânea, ou seja, a manifestação eletrocardiográfica droga-induzida não teria o mesmo significado clínico. No entanto a maioria dos autores prefere ter cautela até que o real papel clínico desses casos esteja definido, preferindo o termo "SBr droga-induzida" [3][4][5][6] . Há relatos de que após uma parada cardiorrespiratória abortada, tanto a presença de SBr espontânea quanto de droga-induzida pode ter significados clínicos semelhantes 7 .…”
unclassified